2004
DOI: 10.1128/iai.72.2.757-765.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sensitized Splenocytes Result in Deleterious Cytokine Cascade and Hyperinflammatory Response in Rats withPneumocystisPneumonia despite the Presence of Corticosteroids

Abstract: The immune response to the opportunistic pulmonary pathogen Pneumocystis can have beneficial and harmful effects on the host despite the presence of corticosteroids. We hypothesized that this deleterious hyperinflammatory response is associated with exaggerated cytokine production. The adoptive transfer of at least 10 7 immune splenocytes reduced the cyst count in rats with corticosteroid-induced pneumocystosis. About 18% of these rats developed clinical illness, an increased lung weight/body weight (LW/BW) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Although a rat model of PCP is usually established by subcutaneous injection cortisone acetate (31)(32)(33), we also successfully constructed PCP model by the intramuscular injection immunosuppressant of dexamethasone sodium phosphate. The higher LW/BW ratio was associated with clinical illness and hyperinflammatory reactions in rats with PCP (34). The study results confirmed that chitosan improved the survival rate of PCP rats and significantly increased weight gain in rats.…”
Section: Figure 13supporting
confidence: 70%
“…Although a rat model of PCP is usually established by subcutaneous injection cortisone acetate (31)(32)(33), we also successfully constructed PCP model by the intramuscular injection immunosuppressant of dexamethasone sodium phosphate. The higher LW/BW ratio was associated with clinical illness and hyperinflammatory reactions in rats with PCP (34). The study results confirmed that chitosan improved the survival rate of PCP rats and significantly increased weight gain in rats.…”
Section: Figure 13supporting
confidence: 70%